2006
DOI: 10.1161/circulationaha.106.643205
|View full text |Cite
|
Sign up to set email alerts
|

Response to Letters Regarding Article, “Effect of Clopidogrel Premedication in Off-Pump Cardiac Surgery: Are We Forfeiting the Benefits of Reduced Hemorrhagic Sequelae?”

Abstract: Because our initial goal was to generate interest in the hemorrhagic complications caused by the use of clopidogrel in cardiac surgery patients, it was with satisfaction that we read the comments of Poston and van der Linden et al regarding our own contribution to the discussion. 1 Both Poston and van der Linden et al propose practicable solutions to deal with the problem. They primarily advocate the perioperative administration of aprotinin as a means of reducing bleeding rates and transfusion requirements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 4 publications
0
32
0
1
Order By: Relevance
“…In the Clopidogrel in Unstable angina to prevent Recurrent Events (CURE) trial (359), patients in whom clopidogrel was stopped fewer than 5 days before CABG surgery had a significantly increased (9.6% versus 6.3% in the placebo arm) rate of major bleeding but no significant difference in perioperative mortality. Kapetanakis et al reported that patients receiving clopidogrel before off-pump coronary artery bypass surgery had an OR of 5.1 (95% CI 2.47 to 10.47; pϽ0.01) with regard to the need for hemostatic reoperation and a significant increase in the need for packed red blood cell and platelet transfusions but no difference in surgical mortality (360). In a series of patients undergoing carotid endarterectomy, a reduction in transcranial Doppler-determined emboli was seen with pretreatment with aspirin and clopidogrel, but no increase in bleeding complications or blood transfusions was seen (361).…”
Section: Risks Associated With Perioperative Antiplatelet Agentsmentioning
confidence: 99%
“…In the Clopidogrel in Unstable angina to prevent Recurrent Events (CURE) trial (359), patients in whom clopidogrel was stopped fewer than 5 days before CABG surgery had a significantly increased (9.6% versus 6.3% in the placebo arm) rate of major bleeding but no significant difference in perioperative mortality. Kapetanakis et al reported that patients receiving clopidogrel before off-pump coronary artery bypass surgery had an OR of 5.1 (95% CI 2.47 to 10.47; pϽ0.01) with regard to the need for hemostatic reoperation and a significant increase in the need for packed red blood cell and platelet transfusions but no difference in surgical mortality (360). In a series of patients undergoing carotid endarterectomy, a reduction in transcranial Doppler-determined emboli was seen with pretreatment with aspirin and clopidogrel, but no increase in bleeding complications or blood transfusions was seen (361).…”
Section: Risks Associated With Perioperative Antiplatelet Agentsmentioning
confidence: 99%
“…In the Clopidogrel in Unstable angina to prevent Recurrent Events (CURE) trial (363), patients in whom clopidogrel was stopped fewer than 5 days before CABG surgery had a significantly increased (9.6% versus 6.3% in the placebo arm) rate of major bleeding but no significant difference in perioperative mortality. Kapetanakis et al reported that patients receiving clopidogrel before off-pump coronary artery bypass surgery had an OR of 5.1 (95% CI: 2.47 to 10.47, P less than 0.01) with regard to the need for hemostatic reoperation and a significant increase in the need for packed red blood cell and platelet transfusions but no difference in surgical mortality (364). In a series of patients undergoing carotid endarterectomy, a reduction in transcranial Dopplerdetermined emboli was seen with pretreatment with aspirin and clopidogrel, but no increase in bleeding complications or blood transfusions was seen (365).…”
Section: Risks Associated With Perioperative Antiplatelet Agentsmentioning
confidence: 99%
“…However such a strategy could delay bypass surgery -if needed -as exposure to clopidogrel within 3-5 days of surgery increases postoperative bleeding and may double the rate of reoperations according to most but not all studies [30][31][32]. Additionally, patients without significant coronary artery disease would have been exposed to aggressive clopidogrel treatment and the risk of bleeding, especially when the femoral approach is used.…”
Section: Timing Of Administrationmentioning
confidence: 99%